Morphological divergence driven by predation environment within and between species of Brachyrhaphis fishes. - Spencer J Ingley; Eric J Billman; Mark C Belk; Jerald B Johnson (PLoS ONE)
Natural selection often results in profound differences in body shape among populations from divergent selective environments. Predation is a well-studied driver of divergence, with predators having a strong effect on the evolution of prey body shape, especially for traits related to escape behavior. Comparative studies, both at the population level and between species, show that the presence or absence of predators can alter prey morphology. Although this pattern is well documented in various species or population pairs, few studies have tested for similar patterns of body shape evolution at multiple stages of divergence within a taxonomic group. Here, we examine morphological divergence associated with predation environment in the livebearing fish genus Brachyrhaphis. We compare differences in body shape between populations of B. rhabdophora from different predation environments to differences in body shape between B. roseni and B. terrabensis (sister species) from predator and predator free habitats, respectively. We found that in each lineage, shape differed between predation environments, consistent with the hypothesis that locomotor function is optimized for either steady swimming (predator free) or escape behavior (predator). Although differences in body shape were greatest between B. roseni and B. terrabensis, we found that much of the total morphological diversification between these species had already been achieved within B. rhabdophora (29% in females and 47% in males). Interestingly, at both levels of divergence we found that early in ontogenetic development, females differed in shape between predation environments; however, as females matured, their body shapes converged on a similar phenotype, likely due to the constraints of pregnancy. Finally, we found that body shape varies with body size in a similar way, regardless of predation environment, in each lineage. Our findings are important because they provide evidence that the same source of selection can drive similar phenotypic divergence independently at multiple divergence levels.